2016
DOI: 10.4236/abb.2016.711045
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics in Pancreatic Cancer Prevention: The Prospects and Challenges

Abstract: Pancreatic cancer is expressed as a disorder of chaos that leads to impairment in biochemical and metabolic physiology of pancreas. It is considered as the most intractable and fatal among all gastrointestinal (GI) cancers. The early occurrence of metastatic spread and the development of intrinsic and acquired resistance during drug treatment limit its prognosis at the right time. The universalized treatment involves surgical resection in which only a minority (<20%) of patients qualify due to advanced stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 139 publications
0
11
0
Order By: Relevance
“…In both animal experiments and human trials, probiotics produce anti-inflammatory metabolites and have been proven to actively facilitate resolution of inflammation in various inflammatory and autoimmune diseases, including ulcerative colitis, rheumatoid arthritis, systemic lupus erythematosus and multiple sclerosis 23 . Research studies have confirmed that the progression of pancreatic cancer is directly related to acute pancreatitis and chronic pancreatitis 24 . To clarify the potential role of probiotics in the treatment of pancreatic cancer, we conducted this animal trial using Kras - driven GEMM of PDAC.…”
Section: Discussionmentioning
confidence: 95%
“…In both animal experiments and human trials, probiotics produce anti-inflammatory metabolites and have been proven to actively facilitate resolution of inflammation in various inflammatory and autoimmune diseases, including ulcerative colitis, rheumatoid arthritis, systemic lupus erythematosus and multiple sclerosis 23 . Research studies have confirmed that the progression of pancreatic cancer is directly related to acute pancreatitis and chronic pancreatitis 24 . To clarify the potential role of probiotics in the treatment of pancreatic cancer, we conducted this animal trial using Kras - driven GEMM of PDAC.…”
Section: Discussionmentioning
confidence: 95%
“…These investigations were performed by involving Propionibacterium , a well-known dairy probiotic. Thus, PC risk could potentially be lowered by decreasing the bioavailability of these neoplastic components [118].…”
Section: Treatment Effortsmentioning
confidence: 99%
“…The impressive potentially probiotics has been assessed in terms of health benefits, but the dilemmatic situation has been existed due to the risk associated with the consumption of probiotics due to their multiple mechanism of action which are dependent on specificity of strain and species utilized [8]. Therefore, substantial efforts are required for thorough understanding of their positive interplay with the host as well as other gut microbial systems at the molecular level [9]. Research studies confirmed that there is fine choreographed molecular networking between the host and probiotics in the form of small "molecular cues".…”
Section: Introductionmentioning
confidence: 99%